The pandemic and the state: Interrogating capacity and response to COVID-19 in West Bengal - Zaad Mahmood; Achin Chakraborty (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
COVID-19 has brought to the fore the issue of state preparedness in mitigating health emergencies. This paper problematizes the received wisdom of greater state capacity in mitigating the severity of the pandemic. Based on a case study of West Bengal, a subnational state of India, it shows that measures of state capacity do not map onto the pandemic response and outcomes very clearly. The three components of state capacity, namely authority, capacity, and legitimacy, show significant variation during the pandemic response. While the state was constrained by fiscal and infrastructural limitations in testing and vaccination, policy response also varied from harsh implementation of lockdown during the initial phase to limp containment due to populist pressures. These limitations notwithstanding, the state managed to avert the worst consequences in terms of COVID-19 deaths when compared to similarly positioned subnational states of India.
Keywords: H11; H12; H75; I18; 330; pandemic; state capacity; policy response; lockdown; COVID-19